Effect of ketanserin on arterial baroreflex-blood pressure control in conscious hypertensive rats - Kong Xian-Bo; Cheng Yong; Su Ding-Feng (Acta Pharmacologica Sinica, 2016)
The effect of ketanserin on arterial baroreflex-blood pressure control (ABR-BP) were studied in conscious freely-moving spontaneously hypertensive rats (SHR) and renovascular hypertensive rats (RVHR). The ABR-BP was measured by using a new method comparing with the pressor responses (in area) to angiotensin II before and after blocking the baroreflex efferent pathway by guanethidine and methyl atropine. It was found that ketanserin enhanced markedly the ABR-BP in both groups of hypertensive rats (SHR: 51% to 74%; RVHR: 59% to 77%). This suggests that the enhancement of ABR-BP may be involved in the anti-hypertensive effects of ketanserin.